Comparison of the Intraocular Pressure Measured Using the New Rebound Tonometer Icare ic100 and Icare TA01i or Goldmann Applanation Tonometer. Issue 2 (February 2019) - Nakakura, Shunsuke; Mori, Etsuko; Fujio, Yuki; Fujisawa, Yasuko; Matsuya, Kanae; Kobayashi, Yui; Tabuchi, Hitoshi; Asaoka, Ryo; Kiuchi, Yoshiaki
Abstract : Purpose: We evaluated the agreement between the intraocular pressure (IOP) values of new rebound tonometer, Icare ic100, and Icare TA01i or Goldmann applanation tonometer (GAT). Methods: We studied one eye each of 106 subjects (57 with primary open-angle glaucoma, 49 healthy subjects). IOP was randomly measured twice with the patient in sitting position using the Icare ic100, Icare TA01i, and GAT. Tonometer measurements were evaluated using Bland-Altman analysis. The relationship between IOP difference (Icare ic100-GAT) and age, sex, disease, axial length, central corneal thickness (CCT), and corneal curvature was investigated using multivariate regression analysis. Results: IOPs measured using Icare ic100, Icare TA01i, and GAT were 11.7±3.0 (mean±standard deviation), 12.2±2.9, and 16.0±3.2 mm Hg, respectively ( P <0.001, one-way analysis of variance). Icare ic100 showed significantly lower IOPs than GAT ( P <0.05), but not than Icare TA01 ( P >0.05; Tukey-Kramer test). Bland-Altman analysis revealed that the mean differences between Icare ic100 and Icare TA01i and those between Icare ic100 and GAT were −0.46 and −4.2 mm Hg, respectively (95% limits of agreement, −3.35 to 2.42 and −10.10 to 1.61 mm Hg, respectively). For IOP differences between Icare ic100 and GAT, parameters selected in the optimal model were CCT (coefficient, 20.3, P =0.029), corneal curvature (3.0, P =0.020), and glaucoma-normal (−1.0, P =0.004). Conclusions: The new rebound tonometer Icare ic100 almost constantly showed IOPs lower than GAT. The difference was affected by CCT, corneal curvature, and disease.